Case Study of ARI in The Mining Industry Environment in Morosi District Konawe Regency - Desriatin, Desriatin; Supodo, Timbul; Sunarsih, Sunarsih; Dewi Marianti, Rita; Sabarudin, Sabarudin (Magister Kesehatan Universitas Mandala Waluya, 2022)
Introduction: Indonesia is among countries rich in minerals (mining) such as gold, silver, copper, coal, oil, and natural gas. The use of natural resources on a large scale by ignoring the preservation of the environment can cause an Acute respiratory infection of negative impacts whether in the short term or long term. Method: The research objective was to determine the level of air pollution produced by coal dust from the coal mining industry activities and to discover information about the relationship between exposures to coal dust and upper respiratory tract infections in the community that lived around the coal mining industry. The research uses a cross-sectional design. Result: The results showed the quality of outdoor air, and the average value for SO2 and NO2 parameters were higher in the designation region than non-designation region. Furthermore, both designation and non-designation regions had the same average H2S parameter but the value of PM10 in the designation region was higher than the designation region. Weather, humidity and wind speed were almostt the same in the two regions. The incidence of upper respiratory tract infections in the exposed locations was higher than non-exposed locations. Conclusion: The incidence of Acute respiratory infection in exposed locations (designated area) is higher compared to non-exposed locations (not designated area).